Morbidity Of Primary Closure of CBD Versus T-Tube Drainage After Laparoscopic Common Bile Duct Exploration - MUHAMMAD NAJAM IQBAL IQBAL; MUHAMMAD ZAFAR MENGAL; MUHAMMAD ANWAR; ARSHAD ABBAS (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Laparoscopic cholecystectomy (LC) and laparoscopic common bile duct exploration (LCBDE) offer one-stage treatment for choledocholithiasis. However, closure of the common bile duct (CBD) either by primary closure (PC) or T-tube drainage (TD) is associated with a higher bile leakage rate. This study aimed to compare the morbidity of primary duct closure with T-tube drainage after LCBDE for choledocholithiasis